Malware Detection and Defense - Babulak, Eduard (IntechOpen, 2023)
Cyber security providers are facing a continuous stream of new, sophisticated cyberattacks on cyber critical infrastructures worldwide. These cyberattacks are often triggered by malware and ransomware. This book presents a collection of selected papers addressing malware detection, which is necessary to create reliable and resilient cyber and computer security mechanisms.